Information System Development of Cattle Weight Recording and Forecasting Using Website-Based Linear Regression - Suprihanto, Didit; Delwizar, Muhammad Arya; Burhandenny, Aji Ery; Harjanto, Arif; Nugroho, Happy; Rumawan, Fatkhul Hani (Diponegoro University, 2025)
Cattle plays an important role in meeting food demand in Indonesia, especially in the livestock sector, where cattle farms must be prepared to provide beef supply to various regions in Indonesia. On the other hand, in East Kalimantan, the demand for beef is also increasing along with the growth of population and economic activity. The role of technology is also quite important in meeting the need for beef. One of them is the use of website information system technology as a recording and reporting application. One of the distributors also involved in cattle farming in East Kalimantan is PT XYZ, which was newly established in 2020. The need for technology includes recording system, reporting system and cattle weight forecasting system. The purpose of this study is to design a web-based application that helps PT XYZ to record, report and predict cattle weight. The application development used Laravel framework to predict the increase in cattle weight using linear regression method. While the methodology used to develop the application was Waterfall method which included the phases of requirement analysis, application design, software development, testing and implementation. The application testing results showed that the application complied with the design that has been implemented and all the functions on the application page worked properly. The cattle weight recording and forecasting information system generated various reports, such as monthly cattle weight progress, monthly cattle sales reports, cattle weight growth forecast analysis, and cattle sales profit reports.